2018
DOI: 10.1038/s41430-018-0116-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of malnutrition on quality of life in patients with systemic sclerosis

Abstract: Severe malnutrition in SSc patients is associated with reduced QoL. Standardized nutritional screening should routinely be conducted to identify the risk of malnutrition in order to enable an intervention with multimodal treatment and avoid the serious consequences associated with severe malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…1 GI in-volvement may lead to malnutrition, which can significantly reduce quality of life and influence both morbidity and mortality of SSc patients. 2 Malnutrition in SSc is associated with disease severity. Disability of hands due to digital ulcers (DUs) and sclerodactyly, making meal preparation and consumption difficult, should also be considered among the factors that negatively impact the nutrition status of SSc patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 GI in-volvement may lead to malnutrition, which can significantly reduce quality of life and influence both morbidity and mortality of SSc patients. 2 Malnutrition in SSc is associated with disease severity. Disability of hands due to digital ulcers (DUs) and sclerodactyly, making meal preparation and consumption difficult, should also be considered among the factors that negatively impact the nutrition status of SSc patients.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms related to GIT involvement, including nausea, vomiting, constipation, gastroesophageal reflux, diarrhea, and weight loss, are present in >90% of SSc patients 1 . GI involvement may lead to malnutrition, which can significantly reduce quality of life and influence both morbidity and mortality of SSc patients 2 . Malnutrition in SSc is associated with disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…This observation, if confirmed by additional studies, may be useful to better diagnose and potentially treat body composition modifications during scleroderma, considering that, unlike nutrition screening and evaluation, 24 echocardiograpy is routinely performed in the assessment and follow‐up of SSc patients.…”
Section: Discussionmentioning
confidence: 69%
“…50 Furthermore, patients with SIBO have higher levels of fecal calprotectin (a bowel inflammatory marker). 50 Approximately 10% of SSc patients can develop malnutrition, 51 with lower levels of serum albumin and vitamin B12 and reduced quality of life. 49,51 Regarding the microbiota composition in SSc and SIBO patients, a study published in 2019 reported an abundance of Odoribacter, Bilophila and Lachnospira species, finding…”
Section: Microbiota Changes In the Lower Digestive Tractmentioning
confidence: 99%